1996
DOI: 10.1155/s1023621x96000139
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling from a Single Row of Compound AngleHoles at High Blowing Ratios

Abstract: Experimental results are presented which describe the development and structure of flow downstream of a single row of holes with compound angle orientations producing film cooling at high blowing ratios. This film cooling configuration is important because similar arrangements are frequently employed on the first stage of rotating blades of operating gas turbine engines. With this configuration, holes are spaced 6d apart in the spanwise direction, with inclination angles of 24 degrees, and angles of orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Ligrani and Lee [48] and Ekkad et al [49] simple injected holes, and it was found that compound angle holes provided better film cooling effectiveness, specifically in the hole near the region compared to streamwise injected holes at the same blowing ratios [48] [49].…”
Section: Compound Angle Of Cylindrical Holementioning
confidence: 99%
“…Ligrani and Lee [48] and Ekkad et al [49] simple injected holes, and it was found that compound angle holes provided better film cooling effectiveness, specifically in the hole near the region compared to streamwise injected holes at the same blowing ratios [48] [49].…”
Section: Compound Angle Of Cylindrical Holementioning
confidence: 99%
“…When implementing a compound angle, the film cooling performance changes as the CRVP changes to a single vortex [8,9]. Lee et al [10] measured the change in the film cooling jet flow for an α value of 35 • , with β ranging from 15 • to 90 • .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cooling jet can be injected from the hole with a spanwise injection angle to the main flow. When a compound angle is implemented, the film cooling performance improves as the CRVP changes to a single vortex [10,11]. Lee et al studied the film cooling flow variation with β ranging from 15 • to 90 • experimentally [12].…”
Section: Introductionmentioning
confidence: 99%